ANALISIS KESALAHAN MENULIS HURUF KAPITAL SISWA KELAS II DI SEKOLAH DASAR NGERI KEBALEN 07 - Auliya Putri, Sheva; Fara Diba Catur Putri; Hafizah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the forms of capitalization errors made by second-grade students at Kebalen 07 Public Elementary School. Capitalization errors are still frequently found in students' writing, so a more in-depth study is needed to determine the types of errors and the factors that influence them. This study uses a qualitative method with a case study design to describe in depth the errors that appear in writing activities. The research subjects consisted of second-grade students as the main informant and second-grade teachers as supporting informants. Data collection techniques were carried out through observation, interviews, and documentation of students' writing results. Data were analyzed using coding techniques to facilitate grouping findings and drawing conclusions. The results of the study indicate that there are still various errors in capitalization, especially in capitalizing at the beginning of sentences, proper names, place names, and the use of capital letters after periods. Factors causing errors include students' lack of understanding of the rules of capitalization, low interest and motivation of students in learning to write, as well as limited time and learning strategies used by teachers. This study emphasizes the importance of strengthening writing learning that is more interesting, focused, and appropriate to students' needs to minimize capitalization errors at the elementary school level.